Clinical Importance of the Persistent Primitive Trigeminal Artery in Vascular Lesions and Its Role in Endovascular Treatment - Wang, Yiheng; Yu, Jinlu (Frontiers in Neurology, 2022)
The persistent primitive trigeminal artery (PPTA) is an important carotid-basilar connection artery. It plays many roles in the development and endovascular treatment (EVT) of vascular lesions; however, our understanding of these roles is insufficient. Therefore, we conducted a PubMed search, performed a review of the relevant extracted literature and cataloged our experience with PPTAs. The findings can be summarized as follows. PPTAs have complex anatomical characteristics and can be classified in a variety of ways, but the modified Saltzman classification is used most often. PPTAs can be associated with cerebrovascular disorders, including aneurysms, brain arteriovenous malformations, trigeminal artery-cavernous fistulas, moyamoya disease, large vessel occlusion, etc. A thorough understanding of the anatomical and angiographic features of this persistent embryonic arterial channel is of utmost importance when making therapeutic decisions for any these pathological conditions. In addition, we provide some significant images and educational cases in this review.